Analisis Pendapatan Petani Jagung di Masa Pandemi Covid-19 - Feliks Arfid Guampe; Yohanes Pasambaka; Join Hengkeng; Silcia Tresya Ponagadi (Hasanuddin University, 2021)
Covid 19 has a very broad impact on socio-economic life globally, nationally and even in rural areas. Sosio-economic restrictions due to Covid-19 affecting agriculture system starting from distribution chain and marketing of agriculture input and output, agriculture processing system and farmers’ income in rural area. The objective of this research is to analyze the income of corn farmers at Peleru village Mori Utara Sub-District Morowali Utara District at Covid-19 Pandemic. This research used qualitative approach with case study. 10 corn farmers was chosen as the key informants. Research result showed that the average cost of corn farming at Peleru village is amount IDR 2.513.510 per Ha per planting season. From the average land area of 1,1 Ha, the farmers obtained a production amount 2.580 kg per planting season. From the price of IDR 2.500 per Kg, the farmers get average income IDR 6.450.000 per planting season. Research result showed that the average net income of the farmers at Peleru village is IDR 3.936.490 per planting season. Keywords: Covid-19; Farmers; Corn; Income.